Definition of success with SEAPI-QMM quality of life ındex after tension free vaginal tape procedure: does validation of score sheet in patient's own language effect the outcome? - (:unkn) unknown (My University, 2008)
0

Introduction: We evaluate the importance of the validation of the SEAPI-QMM quality of life index in patient’s own language to determine the outcome of tension-free vaginal tape operation (TVT®) for stress urinary incontinence. Materials and Methods: SEAPI-QMM quality of life index was translated into Turkish. Patients with stress urinary incontinence and healthy controls were asked to fill out the Turkish version of SEAPI-QMM quality of life index scoring form. Group I consisted of 50 controls Turkish speaking women who were referred consecutively to the clinic for evaluation of diagnoses unrelated to incontinence. The mean age of those patients was 27 (range 22-55). Group II consisted of 48 Turkish speaking women with urodynamic stress urinary incontinence who were planed to undergo TVT® operation with a mean age of 54.8 (range 35-79). Receiver Operating Characteristics (ROC) plots were used to define the detecting cut off or threshold score and Youden`s index was used to detect the best reflecting optimal sensitivity and specificity. After the scoring system was validated and the cut-off values were detected according to the results, Group II patients were reevaluated 1 and 6 months after surgery with the same questionnaire and pad testing. Results: The total score of SEAPI-QMM quality of life index was determined to range from zero to 45. The mean scores were 0.34 (range 0-3) and 23.5 (range 7- 43) in groups I and II, respectively. A patient with a score of four or greater had a disrupted quality of life leading to treatment seeking behavior, with 100% sensitivity and 100% specificity in our patient population. The difference between cut-off values of 4 and 6 of Turkish or original version, respectively, would not change the interpretation of success in patients who underwent tension-free vaginal tape operation (TVT®). To note is that four of 14 patients (28%) who reported dry after the operation also reported a score of more than the cut-off values. Conclusion: Although there is minimal difference between cut-off values of English and Turkish version of SEAPI-QMM quality of life index, it would not effect the interpretation of success after the tension-free vaginal tape operation. Small number of patients may report inconsistent results between the SEAPI-QMM quality of life index score and incontinence episodes; this might effect the interpretation of success after surgery.
Keywords: Üroloji ve Nefroloji